If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(s + -7) = -108 Reorder the terms: 10(-7 + s) = -108 (-7 * 10 + s * 10) = -108 (-70 + 10s) = -108 Solving -70 + 10s = -108 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '70' to each side of the equation. -70 + 70 + 10s = -108 + 70 Combine like terms: -70 + 70 = 0 0 + 10s = -108 + 70 10s = -108 + 70 Combine like terms: -108 + 70 = -38 10s = -38 Divide each side by '10'. s = -3.8 Simplifying s = -3.8
| 72=16t^2+64t+12 | | 5(m+10)=80 | | 6(4s+8)=144 | | 3*x=15-y | | 7(2l+4)=154 | | 3x+99=11x-13 | | 6x-1=12x-59 | | 3(x-2)+2(x-3)=5x-12 | | a+b+c+d+e=1139 | | 2x^2-9y^2=0 | | 3y/2x=x/3y | | 6(4w-2)+5=4w-3 | | 16.5*x-0.98*(x^2)-24.22=0 | | -1x+4=-4+25x | | 6x^3+42x^2+60x+21=0 | | 5x+107=10x-8 | | 5t+20=10 | | 10x=7p | | x(3.14)=6 | | 10-28=62 | | 3/x=25 | | 6-0.5x=8-2.5x | | 15c+90=-90 | | z+0.2z+0.6=6(z-6.3) | | A-7+3-4a=-4-3a | | 3.5x-4=3 | | 14x^2+4+3x-12x^2-3+11x= | | (x+5)2-529=0 | | 4x-7=9x+6 | | (3y-x)(2x+y)= | | Cot*4x=-1 | | 4(3+y)= |